Social-Ecological Predictors of Opioid Use Among Adolescents With Histories of Substance Use Disorders - Nichols, Lindsey M.; Pedroza, Jonathan A.; Fleming, Christopher M.; O’Brien, Kaitlin M.; Tanner-Smith, Emily E. (Frontiers in Psychology, 2021)
Adolescent opioid misuse is a public health crisis, particularly among clinical populations of youth with substance misuse histories. Given the negative and often lethal consequences associated with opioid misuse among adolescents, it is essential to identify the risk and protective factors underlying early opioid misuse to inform targeted prevention efforts. Understanding the role of parental risk and protective factors is particularly paramount during the developmental stage of adolescence. Using a social-ecological framework, this study explored the associations between individual, peer, family, community, and school-level risk and protective factors and opioid use among adolescents with histories of substance use disorders (SUDs). Further, we explored the potential moderating role of poor parental monitoring in the associations between the aforementioned risk and protective factors and adolescent opioid use. Participants included 294 adolescents (Mage = 16 years; 45% female) who were recently discharged from substance use treatment, and their parents (n=323). Results indicated that lifetime opioid use was significantly more likely among adolescents endorsing symptoms of Antisocial Personality Disorder or whose parents reported histories of substance abuse. Additionally, adolescents reporting more perceived availability of substances were significantly more likely to report lifetime opioid use compared to those reporting lower perceived availability of substances. Generally, results showed that social-ecological risk factors were not significant indicators of opioid use in this high-risk population of adolescents. We discuss these findings in terms of continuing care options for adolescents with SUD histories and family-based interventions, including practical implications for working with families of adolescents with SUD histories.